2015
DOI: 10.1103/physreva.92.023847
|View full text |Cite
|
Sign up to set email alerts
|

SU(1,1)-type light-atom-correlated interferometer

Abstract: The quantum correlation of light and atomic collective excitation can be used to compose an SU(1,1)-type hybrid light-atom interferometer, where one arm in the optical SU(1,1) interferometer is replaced by the atomic collective excitation. The phase-sensing probes include not only the photon field but also the atomic collective excitation inside the interferometer. For a coherent squeezed state as the phase-sensing field, the phase sensitivity can approach the Heisenberg limit under the optimal conditions. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The LCC J n2 (n a2 ,n b2 ) is positive, and J n2 (n a2 ,n b2 ) ranges between 0 and 1. This decorrelation point (φ = 0) J x2 (x a2 ,x b2 ) = 0 is very important for atom-light hybrid interferometer using the homodyne detection [50]. At this point (φ = 0) the noise of output field [ (∆x a2 ) 2 = 1/4] is the same as that of input field and it is the lowest in our scheme as shown in Fig.…”
Section: The Correlations Of Atom-light Hybrid Interferometermentioning
confidence: 81%
See 1 more Smart Citation
“…The LCC J n2 (n a2 ,n b2 ) is positive, and J n2 (n a2 ,n b2 ) ranges between 0 and 1. This decorrelation point (φ = 0) J x2 (x a2 ,x b2 ) = 0 is very important for atom-light hybrid interferometer using the homodyne detection [50]. At this point (φ = 0) the noise of output field [ (∆x a2 ) 2 = 1/4] is the same as that of input field and it is the lowest in our scheme as shown in Fig.…”
Section: The Correlations Of Atom-light Hybrid Interferometermentioning
confidence: 81%
“…In this section, we review the different processes of the atom-light interferometer [49,50] as shown in Fig. 1(a)-(c), where two Raman systems replaced the BSs in the traditional MZI.…”
Section: The Model Of Atom-light Hybrid Interferometermentioning
confidence: 99%
“…Recently, the atom-light hybrid interferometer has drawn considerable interest because it is sensitive to both optical and atomic phase shift [26][27][28][29][30][31]. There are two types of atom-light hybrid interferometers, which have been also demonstrated experimentally by our group.…”
Section: Introductionmentioning
confidence: 86%
“…1(a). There are two types of atom-light interferometers [28,29,32,33]. The first type is an analog of Mach-Zehnder/Michaelson optical interferometer but with atom-light mixer replacing regular beam splitters for linear superposition of atomic waves and optical waves [27,29].…”
Section: Qnd Measurement Of Photon Number By Atom-light Interferometersmentioning
confidence: 99%